Mechanosensitive Regulation of Fibrosis - Shuying Yang; Sergey V. Plotnikov (Cells, 2021)
Cells in the human body experience and integrate a wide variety of environmental cues. A growing interest in tissue mechanics in the past four decades has shown that the mechanical properties of tissue drive key biological processes and facilitate disease development. However, tissue stiffness is not only a potent behavioral cue, but also a product of cellular signaling activity. This review explores both roles of tissue stiffness in the context of inflammation and fibrosis, and the important molecular players driving such processes. During inflammation, proinflammatory cytokines upregulate tissue stiffness by increasing hydrostatic pressure, ECM deposition, and ECM remodeling. As the ECM stiffens, cells involved in the immune response employ intricate molecular sensors to probe and alter their mechanical environment, thereby facilitating immune cell recruitment and potentiating the fibrotic phenotype. This powerful feedforward loop raises numerous possibilities for drug development and warrants further investigation into the mechanisms specific to different fibrotic diseases.